The best of pro basketball - Doeden, Matt. (Mankato, Minn. : Capstone Press, 2010)
"Presents some of the best moments and players in professional basketball history"--Provided by publisher.
Best scorer -- Most points by a player in a game -- Best shootout -- Best comeback -- Best rebounder -- Best steal -- Best last-second shot -- Most amazing shot -- Best three-point shooter.
Includes bibliographical references (p. 23) and index.
Keywords: Basketball -- United States -- History -- Juvenile literature; Basketball players -- United States -- History -- Juvenile literature; Basketball -- United States -- History; Basketball players -- United States -- History; Sports